2008
DOI: 10.1590/s0100-29452008000100017
|View full text |Cite
|
Sign up to set email alerts
|

Uso de quitosana e embalagem plástica na conservação pós-colheita de pêssegos 'Douradão'

Abstract: , ANDRESSA ARAUJO PICOLI 4 , GLAUCO DE SOUZA ROLIM 3 RESUMO -Este trabalho teve como objetivo avaliar a qualidade do pêssego cv. Douradão, quando aplicados tratamentos pós-colheita, associada à temperatura adequada de refrigeração. Os tratamentos foram: aplicação de quitosana a 1%; embalagem de polietileno e controle (não-tratado e sem embalagem plástica). Após serem embalados em caixas de papelão e armazenados a 3o C e 90% UR, durante 14; 21 e 28 dias, foram transferidos para condições-ambiente, permanec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
1
7
0
11
Order By: Relevance
“…Portanto, era esperado que os recobrimentos tivessem pouca interferência nesta variável. Santos et al (2008) avaliando pêssegos 'Douradão' recobertos com quitosana 1%, verificaram que esta não reduziu a perda de massa fresca, ocorrendo as maiores perdas mesmo quando comparado ao controle. Segundo Banks et al, (1993) a perda de massa fresca deve ser estudada em conjunto com outras características para a avaliação do processo de amadurecimento, pois a barreira à saída de água também pode impedir a troca de gases, bloqueando com isso o processo de amadurecimento e conduzindo à anaerobiose das frutas.…”
Section: Resultsunclassified
“…Portanto, era esperado que os recobrimentos tivessem pouca interferência nesta variável. Santos et al (2008) avaliando pêssegos 'Douradão' recobertos com quitosana 1%, verificaram que esta não reduziu a perda de massa fresca, ocorrendo as maiores perdas mesmo quando comparado ao controle. Segundo Banks et al, (1993) a perda de massa fresca deve ser estudada em conjunto com outras características para a avaliação do processo de amadurecimento, pois a barreira à saída de água também pode impedir a troca de gases, bloqueando com isso o processo de amadurecimento e conduzindo à anaerobiose das frutas.…”
Section: Resultsunclassified
“…Among the methods of postharvest preservation, coatings and toppings are used on fruits in order to extend their preservation associated or not with the use of low temperatures. Temperature is probably the most important factor that affects the storage period of fruits and vegetables, because it regulates the rates of all physiological and biochemical processes (SANTOS et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the acidity of the chitosan coating solution could produce damage on the fruit surface (ASSIS; ALVES, 2002, p. 5). Hojo, Durigan and Hojo (2011) and Santos et al (2008) found that the increasing weight loss during storage of lychees and peaches was produced by the chemical reagents found in the commercial chitosan formulation as well as on the coating additives. However, most of researchers conclude that chitosan coating applications reduce the weight loss of food (JIANG;FENG;LI, 2012;PARK et al, 2005).…”
Section: Weight Lossmentioning
confidence: 99%
“…However, others studies reported the total acidity reduction on the coated fruits during storage due to the fruit ripening what caused a organic acid consumption on the respiration (DANIELI et al, 2002), for example using coatings on blueberries, strawberries, apples and lychees (DUAN et al, 2011;HAN et al, 2005;HOJO;DURIGAN;HOJO, 2011;SANTOS et al, 2008 ).…”
Section: Titratable Aciditymentioning
confidence: 99%